EQUINE ASSISTED THERAPY (International Journal of Food and Nutritional Sciences, 2022)
Equine Therapy is also called as Equine Assisted Psychotherapy is a form of therapy involving interaction between horses and patients. It involves activities such as feeding, grooming of hair and leading a horse which are supervised by a specialist in mental health with a support of horse professional. The major goal of the therapy is to increase skill and attributes like accountability, self confidence, responsibility and problem solving skills. It also helps in behavioral and emotional changes. From the ancient Greek horses are used as therapeutic aid. The literature were documented that the therapy was prescribed for some diseases like Gout, Neurological Disorders and for persons with low morale. The therapy was introduced in 1946, at Scandinavia after an outbreak of poliomyelitis. This therapy has having some supportive evidence for its effectiveness against managing some conditions like, Anxiety, ADHD, Addiction Disorder, Post Traumatic Stress Disorder etc. when an individual riding a horse, it stimulates the areas where they never had exercise thus improves balance and mobility of the body. This therapy helps the individuals to develop a work ethic, identify and process feelings. This therapy also helps to develop Trust on each other. Peoples with spinabifida, Scoliosis or Down syndrome should have a consultation before getting this therapy.